2018
DOI: 10.2337/dc18-0253
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Differs in Composition and Functionality Between Children With Type 1 Diabetes and MODY2 and Healthy Control Subjects: A Case-Control Study

Abstract: Gut microbiota in type 1 diabetes differs at taxonomic and functional levels not only in comparison with healthy subjects but fundamentally with regard to a model of nonautoimmune diabetes. Future longitudinal studies should be aimed at evaluating if the modulation of gut microbiota in patients with a high risk of type 1 diabetes could modify the natural history of this autoimmune disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
196
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(215 citation statements)
references
References 43 publications
15
196
3
1
Order By: Relevance
“…However, conflicting data with regard to F/B ratio in individuals diagnosed with T1D have been published too (28,29), which may be attributed to different sample sizes, data analysis approaches, and geographical location. Another common gut microbiome shift associated with the T1D development is the decreased microbial diversity, which has been reported both in T1D children (30,31) and in autoantibodypositive children (26,27,32). It was further found that the decline in bacterial diversity was specific to seroconverters that eventually developed into T1D but not in undeveloped seroconverters (33).…”
Section: Aberrant Gut Microbiota Composition In Human T1dmentioning
confidence: 86%
See 2 more Smart Citations
“…However, conflicting data with regard to F/B ratio in individuals diagnosed with T1D have been published too (28,29), which may be attributed to different sample sizes, data analysis approaches, and geographical location. Another common gut microbiome shift associated with the T1D development is the decreased microbial diversity, which has been reported both in T1D children (30,31) and in autoantibodypositive children (26,27,32). It was further found that the decline in bacterial diversity was specific to seroconverters that eventually developed into T1D but not in undeveloped seroconverters (33).…”
Section: Aberrant Gut Microbiota Composition In Human T1dmentioning
confidence: 86%
“…A decrease in Bifidobacterium was also reported in T1D subjects by several studies. In a study investigating the bacterial compositional differences among children with T1D and maturity-onset diabetes of the young 2 (MODY2) and healthy control subjects by 16S ribosomal RNA (rRNA) gene sequencing, the authors concluded that T1D children presented with a reduced level of Bifidobacterium, and perhaps even more interestingly, it was observed that the intestinal microbiota profile of T1D patients was different from not only healthy subjects but also subjects with MODY2 (30). Another study also using 16S rRNA gene sequencing concluded the similar trends regarding Bifidobacterium (37).…”
Section: Aberrant Gut Microbiota Composition In Human T1dmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of dysbiosis have often been assessed by changes in richness and diversity with variable findings in different disease conditions. For instance, the richness and diversity of gut microbiota was found to be reduced in arteriosclerosis, hypertension [21], diabetic patients [22] and animal model, whereas increased diversity was associated with atrial fibrillation [23] myocardial infarction, stroke and transient ischemic attacks. Interestingly alterations associated with autism [24] and obesity [25] was found to be inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there was an increased abundance of Ruminococcus and Bacteroides and a decreased abundance of Bifidobacterium and Faecalibacterium in T1DM; the relative abundance of Prevotella was increased in MODY2, but Ruminococcus and Bacteroides were reduced. Moreover, intestinal permeability was increased in MODY2 and T1DM, accompanied by increased serum proinflammatory cytokines (e.g., IL-1β, IL-6, and TNF-α) and LPS in T1DM [115]. The inflammasome complexes NLRP3 is a multiprotein complex that recognizes microbial-associated molecular patterns and participates in proinflammatory pathways, and the mice lack these complexes show altered intestinal microbial composition and lead to NAFLD [116].…”
Section: Nlrp3 and The Microbiomementioning
confidence: 99%